Perinatal and early life factors and asthma control among preschoolers: a population-based retrospective cohort study - Maria B Ospina; Francine M Ducharme; Susan Crawford; Jesus Serrano-Lomelin; Anne Hicks; Rhonda J Rosychuk; Radha Chari; Anita L Kozyrskyj; Linn E Moore; Jeffery Bakal (BMJ Open Respiratory Research, 2023)
Background Preventing poor childhood asthma control is crucial for short-term and long-term respiratory health. This study evaluated associations between perinatal and early-life factors and early childhood asthma control.Methods This retrospective study used administrative health data from mothers and children born 2010–2012 with a diagnosis of asthma before age 5 years, in Alberta, Canada. The outcome was asthma control within 2 years after diagnosis. Associations between perinatal and early-life factors and risk of partly and uncontrolled asthma were evaluated by multinomial logistic regression.Results Of 7206 preschoolers with asthma, 52% had controlled, 37% partly controlled and 12% uncontrolled asthma 2 years after diagnosis. Compared with controlled asthma, prenatal antibiotics (adjusted risk ratio (aRR): 1.19; 95% CI 1.06 to 1.33) and smoking (aRR: 1.18; 95% CI 1.02 to 1.37), C-section delivery (aRR: 1.11; 95% CI 1.00 to 1.25), summer birth (aRR: 1.16; 95% CI 1.00 to 1.34) and early-life hospitalisation for respiratory illness (aRR: 2.24; 95% CI 1.81 to 2.76) increased the risk of partly controlled asthma. Gestational diabetes (aRR: 1.41; 95% CI 1.06 to 1.87), C-section delivery (aRR: 1.18; 95% CI 1.00 to 1.39), antibiotics (aRR: 1.32; 95% CI 1.08 to 1.61) and hospitalisation for early-life respiratory illness (aRR: 1.65; 95% CI 1.19 to 2.27) were associated with uncontrolled asthma.Conclusion Maternal perinatal and early-life factors including antibiotics in pregnancy and childhood, gestational diabetes, prenatal smoking, C-section and summertime birth, and hospitalisations for respiratory illness are associated with partly or uncontrolled childhood asthma. These results underline the significance of perinatal health and the lasting effects of early-life experiences on lung development and disease programming.